Study on Characteristics of Mining Earthquake in Multicoal Seam Mining under Thick and Hard Strata in High Position - Shuli Wang; Guangli Zhu; Kaizhi Zhang; Lei Yang (Shock and Vibration)
Rock burst has become one of the most serious world’s problems in coal resources mining, and fracture and movement of thick and hard strata in high position is the main reason to induce strong mining earthquake and rock burst. Multicoal seam mining of 10302 working face in Baodian coal mine is selected as an engineering background, which has thick and hard strata in high position. Using SOS microseismic monitoring system to collect microseismic events and date during multicoal seam mining, characteristic and difference of microseismic in multicoal seam mining under thick and hard rock in high position is analyzed systematically. The main research work is as follows: reveal temporal and spatial distribution and evolution law of microseismic and analyze difference and correlation of microseismic in multicoal mining under thick and hard strata in high position, especially the relationship between mining earthquake with high energy and fracture and movement of thick and hard strata in high position. With the characteristics of microseismic, rock burst mechanism and difference induced by thick and hard strata in high position are discussed. The research and achievement could make guidance to multicoal seam mining safety under thick and hard strata in high position.